2020
DOI: 10.1590/1678-4324-2020180735
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening of Callus and Cell Suspensions Cultures of Thevetia peruviana

Abstract: Thevetia peruviana is an ornamental shrub grown-up in many tropical region of the world. This plant produces secondary metabolites with biological properties of interest for the pharmaceutical industry. The objective was to determine the secondary metabolites profile of callus and cell suspension cultures of T. peruviana and compare them with those from explant (fruit pulp). Extracts in 50% aqueous ethanol and ethyl acetate were prepared. The phytochemical analysis was performed using standard chemical tests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Researches conducted by Arias and coauthors [25] and Tabata [26] in in vitro cultures of T. peruviana reported the increase of cardiotonic glycosides and peruvosides using MeJa and SA elicitors. A recent study published by Mendoza and coauthors [7] reported cardiac glycosides, phenolic, and flavonoids compounds in cell suspension cultures of T. peruviana during the exponential grown phase. Considering that secondary metabolites are of pharmaceutical interest, it is necessary to explore ways of large-scale production at industrial levels, which have already been achieved with plants such as Taxus sp.…”
Section: Graphical Abstractmentioning
confidence: 99%
See 2 more Smart Citations
“…Researches conducted by Arias and coauthors [25] and Tabata [26] in in vitro cultures of T. peruviana reported the increase of cardiotonic glycosides and peruvosides using MeJa and SA elicitors. A recent study published by Mendoza and coauthors [7] reported cardiac glycosides, phenolic, and flavonoids compounds in cell suspension cultures of T. peruviana during the exponential grown phase. Considering that secondary metabolites are of pharmaceutical interest, it is necessary to explore ways of large-scale production at industrial levels, which have already been achieved with plants such as Taxus sp.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…The explants were extracted from fruit pulp and put aseptically in sterile solid Schenk & Hildebrandt (SH) medium [30], supplemented with 2 mg L -1 2,4-dichlorophenoxyacetic acid (2,4-D), 0.5 mg L -1 kinetin, 30 g L -1 sucrose, 7 g L -1 agar and 1 g L -1 myoinositol (pH 5.8), sterilized at 121°C and 1 atm during 20 min. Callus cultures were kept in photoperiod of light 12 hdarkness 12 h. Sub-cultures were made every three weeks until obtaining friable callus [7].…”
Section: Callus Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, metabolites (including alkaloids, flavonoids, polyphenols, terpenes, triterpenes, cardiac glycosides, paclitaxel and related taxoids) with various physiologically active functions can be produced using this method 14 , 15 . Therefore, the plant tissue culture technique is actively studied to continuously improve the production of biologically valuable high-quality materials 16 - 18 . Nonetheless, research on the selection and function of plant callus materials that can be used as functional cosmetic ingredients is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The study and research of alternative methods of obtaining compounds with useful and unique characteristics from plant materials is relevant. The biosynthesis of in vitro transformed callus, cell suspension, and root cultures (hairy roots), from the point of view of the controlled production of biologically active substances with desired properties, has potential, and is of interest to both researchers and producers [25].…”
Section: Introductionmentioning
confidence: 99%